2006
DOI: 10.1128/jvi.01098-06
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Protective Immune Response against Viral Nervous Necrosis in the European Sea Bass Dicentrarchus labrax by Using Betanodavirus Virus-Like Particles

Abstract: Betanodaviruses are causative agents of viral nervous necrosis (VNN), a devastating disease of cultured marine fish worldwide. Virus particles contain a single type of coat protein that spontaneously assembles into virus-like particles (VLPs) when expressed in a baculovirus expression system. In the present study, the immunogenicity of betanodavirus VLPs and the protection they confer against VNN in the European sea bass Dicentrarchus labrax were investigated. Enzyme-linked immunosorbent assay and seroneutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 30 publications
6
49
0
1
Order By: Relevance
“…The open reading frame (ORF) contains a 982-amino-acid with a calculated molecular mass of 110.74 kDa. On the other hand, the smaller segment, RNA2 (1433 nt) having a G?C content of 53.24 % contains a 338-amino-acid major ORF which encodes the coat protein with a calculated molecular mass of 37.059 kDa flanked by 26 nt 5 0 -NTR and a 390 nt 3 0 -NTR [19,75,107,118]. RNA2 forms a major ORF of capsid protein and consists of a highly conserved region and a variable region.…”
Section: Genome Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The open reading frame (ORF) contains a 982-amino-acid with a calculated molecular mass of 110.74 kDa. On the other hand, the smaller segment, RNA2 (1433 nt) having a G?C content of 53.24 % contains a 338-amino-acid major ORF which encodes the coat protein with a calculated molecular mass of 37.059 kDa flanked by 26 nt 5 0 -NTR and a 390 nt 3 0 -NTR [19,75,107,118]. RNA2 forms a major ORF of capsid protein and consists of a highly conserved region and a variable region.…”
Section: Genome Organizationmentioning
confidence: 99%
“…To ensure that the fish are as healthy as possible, a useful and practical approach would be vaccination of fish and boosting their immune system. Various types of vaccines have been developed such as formalininactivated vaccine, subunit vaccine with recombinant coat protein of betanodavirus and nodavirus-like particle vaccine [58,74,111,116,118,121,124]. Vaccination trials have shown protection efficacy against betanodavirus infection.…”
Section: Disease Control Strategiesmentioning
confidence: 99%
“…Under these circumstances, several kinds of fish nodavirus vaccines have been developed, such as formalin-inactivated vaccine, subunit vaccine with a recombinant coat protein, virus-like particle vaccine, etc. (Húsgar7 et al 2001, Tanaka et al 2001, Yuasa et al 2002, Sommerset et al 2005, Yamashita et al 2005, Liu et al 2006, Thiéry et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that icosahedral, virus-like particles (VLPs) represent highly effective platforms for the development of novel vaccines (4,19,21,24,30,31,38). Icosahedral virus particles are known to be strongly immunogenic based on the repetitive array of their component proteins, particulate nature, and ability to appropriately stimulate the innate immune response.…”
mentioning
confidence: 99%